Measuring Early Childhood Development Among 4–6 Year Olds: The Identification of Psychometrically Robust Items Across Diverse Contexts - Pushparatnam, Adelle; Luna Bazaldua, Diego Armando; Holla, Alaka; Azevedo, João Pedro; Clarke, Marguerite; Devercelli, Amanda (Frontiers in Public Health, 2021)
The last fifteen years have seen an explosion of measurement tools for assessing the development of young children in low- and middle- income countries. This paper builds on and contributes to that literature by identifying a core set of caregiver-report items and a core set of direct assessment items that measure key developmental domains for children aged 4-6 (48-83 months) and that demonstrate adequate psychometric properties across diverse contexts, the first in this age group to the authors’ knowledge. Data were harmonized from previous early childhood measurement efforts in 12 countries that all used the same base measurement tool. Data analyses yielded 20 caregiver report items and 87 child direct assessment items (grouped into 17 tasks) that show strong item-level statistics across countries and that cover the domains of early literacy, early numeracy, executive functioning, and social-emotional competencies. Next steps include adding data and items from other measurement tools to the same analytical framework and field testing across a number of contexts and early childhood measurement efforts. The vision is for the resulting core sets of items, along with guidance on data collection, management, and analysis, to serve as global public goods so that they can (i) present a starting point for linking across different early childhood measurement tools for children aged 4-6; (ii) increase quality across measurement efforts; and (iii) facilitate the scale up of early childhood measurement . When supplemented with items that capture local contexts and their measurement needs, these core sets of items should help to advance understanding of universal and context-specific factors that underlie child development and thus help policymakers make decisions that ensure children receive the quality early childhood care and education they need in order to reach their full potential.